Purity in the Gospel of John: early Jewish tradition, christology, and ethics - Rogan, Wil (Library of New Testament studies, 2023)
Wil Rogan argues that, contrary to twentieth-century interpretation, the Fourth Gospel did not replace purity with faith in Jesus. Instead, as with other early Jewish writings, its discourse about purity functions as a way to make sense of life before God in the world. He suggests that John's Gospel employs biblical and early Jewish traditions of purity associated with divine revelation and Israel's restoration to narrate how God's people are prepared for the coming of Jesus and enabled by him to have life with God characterized by love. After evaluating different theories of purity for the interpretation of the Fourth Gospel, Rogan explores John the Baptist as an agent of ritual purification, Jesus as the agent of moral purification, and the disciples of Jesus as ones who are (or are not) made morally pure by Jesus. While purity is not one of the Fourth Gospel's primary focuses, Rogan stresses that the concept figures into some of its most significant claims about Christology, the doctrine of salvation, and ethics. Through purity, the Fourth Gospel guards continuity with the past while placing surprising conditions on participation in Israel's future